Looking for Answers to Food Loss and Waste Management in Spain from a Holistic Nutritional and Economic Approach - Abejon-Elias, R (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The generation of food loss and waste (FLW) is a global problem for worldwide politics. About one‐third of the food produced ends up in the rubbish before it is consumed. For this reason, it is essential to design and implement new strategies along the food supply chain (FSC) with the aim of reducing this FLW at each stage. However, not only mass quantification should be consid-ered, but also economic and nutritional performance. The novelty of this study is the definition of a methodology based on the “distance to target” approach by means of multi‐objective optimization to evaluate the economic and nutritional cost produced by this FLW. This methodology was applied to the Spanish food basket in 2015. The results revealed that 80% of the total FLW generated in economic and nutritional terms is concentrated in the agricultural production (53.3%) and consumption (26.3%) stages. In the first stages of the FSC, fruits (Dn eq.= 0.7), cereals (Dn eq.= 0.61), and vegetables (Dn eq.= 0.57) were the furthest from the distance target due to the great amount of FLW generated. Moreover, according to the normalized weighted distances obtained from the minimi-zation of economic and nutritional cost, pulses (Dn eq. = 0.05–0.03) and eggs (Dn eq. = 0.02) were the more efficient food categories. The methodology described in this study proposes a single index to quantify the economic and nutritional cost of different food categories to facilitate the decision-making process. This index makes possible the definition of reduction strategies focused on specific food categories and depending on the FSC stage. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.